Penerapan Kriptografi AES untuk Pengamanan Data Pasien pada Sistem Rekam Medis Digital di Puskesmas Surulangun - Riskal; Alda Septiani; Rayhan Ferliansyah; Riya Triutami (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
The development of information technology in the health sector encourages the use of digital medical record systems to improve efficiency in patient data management. However, the digitization of medical data also poses risks to the security and confidentiality of sensitive patient information, such as potential data leaks, misuse, and access by unauthorized parties. Therefore, this study discusses the application of the Advanced Encryption Standard (AES) cryptographic algorithm as a solution to improve patient data security in the digital medical record system at the Surulangun Community Health Center. This study aims to apply the AES algorithm in the process of securing patient data so that data stored in the system remains confidential. The research method used is an implementation method by applying the AES algorithm to the data encryption and decryption process in the digital medical record system so that data stored in the database is in encrypted form. The results of the study indicate that the application of the AES algorithm can improve patient data security by encrypting data before being stored in the database and decrypting it again when accessed by authorized users. With this mechanism, patient data is better protected from potential data theft and manipulation. Based on the results of this study, it can be concluded that the application of AES cryptography in the digital medical record system at the Surulangun Community Health Center is effective in increasing security and maintaining the confidentiality of patient data, thereby supporting safer and more reliable health information management.